Impact of information technology on the factors constituting the competitive ability of 2- and 3- star hotels in Hanoi - Huong Giang Vu; Thai An Ngo; Thu Trang Truong; Viet Anh Nguyen (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: To examine the impact of information technology on the competitive ability of 2- and 3-star hotels in Hanoi. Method: This study used desk research and surveys to collect data. Then, the data was processed by using SPSS 20.0 and AMOS 20.0 with the Reliability Testing, the Exploratory Factor Analysis (EFA), the Confirmatory Factor Analysis (CFA) and the linear SEM analysis. Result: The results show that information technology has positive impacts on the 05 factors that constituting the competitive ability of 2- and 3-star hotels in Hanoi: market-oriented ability, marketing ability, organizational management ability, resource mobilizing ability, social capability. Contribution: The research addresses a significant and relevant area in the field of hospitality and technology while providing valuable insights into how information technology adoption can enhance the competitive ability of 2- and 3-star hotels in Hanoi. Moreover, the findings may have implications for policymakers and industry stakeholders. It could inform government initiatives or industry associations on how to support IT adoption and competitive ability in the hospitality sector. At the same time, it can also contribute to the broader discussion on the role of technology in the hospitality industry and its implications for both businesses and consumers in future researches.